Deaths Rise in Good Economic Times: Evidence From the OECD - Ulf-G. Gerdtham; Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2003)
This study uses aggregate data for 23 OECD countries over the 1960-1997 period to examine the relationship between macroeconomic conditions and fatalities. The main finding is that total mortality and deaths from several common causes increase when labor markets strengthen. For instance, controlling for year effects, location fixed effects, country-specific time trends and demographic characteristics, a one percentage point decrease in the national unemployment rate is associated with a 0.4 percent rise in total mortality and 0.4, 1.1, 1.8, 2.1 and 0.8 percent increases in deaths from cardiovascular disease, influenza/pneumonia, liver disease, motor vehicle fatalities and other accidents. These results are consistent with the findings of other recent research and cast doubt on the hypothesis that economic downturns have negative effects on physical health.
Keywords: E32; J2; I12; 330; business cycles; mortality; health; Sterblichkeit; Konjunktur; Schätzung; OECD-Staaten